Managing the work situation : a phenomenological approach to organization and management in a complex world of work - Klemsdal, Lars (Routledge, 2025)
"Managing the Work Situation outlines a perspective on how organization and management in the contemporary world of work happens as active everyday accomplishments by workers and managers, facing and handling complex work situations with an excess of expectations. Based on philosophical and sociological phenomenology, notably Jean-Paul Sartre's and Erving Goffman's works, the book coins a situation-centric perspective on organization and management, and the concept of 'situational sensemaking', as the driving mechanism of organization as well as the focus of management - characterised as 'situation management'. The book addresses an academic audience with interests in organization and management of work, both theoretically and practically. A prime audience will be (academic and executive) master students in organization and management"-- Provided by publisher.
Keywords: Management.; Organizational effectiveness.; Organizational behavior.; elektronické knihy; electronic books